Relationship between communication skills and gross motor function in preschool-aged children with cerebral palsy - Coleman, A.; Weir, K.; Ware, R.; Boyd, Roslyn (2013)
Objectives: To explore the communication skills of children with cerebral palsy (CP) at 24 months' corrected age with reference to typically developing children, and to determine the relationship between communication ability, gross motor function, and other comorbidities associated with CP. Design: Prospective, cross-sectional, population-based cohort study. Setting: General community. Participants: Children with CP (N=124; mean age, 24mo; functional severity on Gross Motor Function Classification System [GMFCS]: I=47, II=14, III=22, IV=19, V=22). Interventions: Not applicable. Main Outcome Measures: Parents reported communication skills on the Communication and Symbolic Behavior Scales Developmental Profile (CSBS-DP) Infant-Toddler Checklist. Two independent physiotherapists classified motor type, distribution, and GMFCS. Data on comorbidities were obtained from parent interviews and medical records. Results: Children with mild CP (GMFCS I/II) had mean CSBS-DP scores that were 0.5 to 0.6 SD below the mean for typically developing peers, while those with moderate-severe impairment (GMFCS III-V) were 1.4 to 2.6 SD below the mean. GMFCS was significantly associated with performance on the CSBS-DP (F=18.55, P<.001), with gross motor ability accounting for 38% of the variation in communication. Poorer communication was strongly associated with gross motor function and full-term birth. Conclusions: Preschool-aged children with CP, with more severe gross motor impairment, showed delayed communication, while children with mild motor impairment were less vulnerable. Term-born children had significantly poorer communication than those born prematurely. Because a portion of each gross motor functional severity level is at risk, this study reinforces the need for early monitoring of communication development for all children with CP.